Peningkatan Hasil Belajar PAI Dengan Metode Maching Card di Kelas IV UPTD SDN 07 Kubang - Cita Siskanela; Salmiwati Salmiwati; Rina Mala Putri (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) in class IV UPTD SDN 07 Kubang students by using the Problem-Based Learning (PBL) method. The background of this study is the low learning outcomes of PAI students, which is caused by the lack of active involvement of students in the learning process. The PBL method was chosen because it is able to increase student involvement in solving real problems that are relevant to everyday life, thus encouraging deeper understanding and direct application of concepts. This study used a Classroom Action Research (PTK) approach with two cycles, which involved planning, implementation, observation, and reflection. The results showed that the application of the PBL method can significantly improve student learning outcomes. In cycle I, the students' average score increased from before, and in cycle II there was a higher increase, which showed the effectiveness of the PBL method in improving PAI learning outcomes. Keywords: , ,